شیکردنەوەی تەنز بەپێی تیۆری کردەقسەییەکان (پەندی پێشینان بەنمونە) - اسماعیل, م.شێرکۆ محمد; عومەر, پ.ی.د نەوزاد ئەنوەر (Sulaimani Journal for Humanities, 2023)
This research under the title Analysis of Satire according to the theory of speech act (Byword) In this research paper meaning and purpose of Stair is analyzed especially those meanings that are hidden in funny Bywords and Satirical that have pragmatic purposes. In the pragmatic the focus is on speech act, it is so as to dedicate the meaning of satirical Bywords and find the speech act kind, because the value of speech act is not finding the actual grammatical meaning, but according to the purpose of the speaker at specific situation that the Bywords have been spelled out, the researcher have thought that the speech acts clearly are exist in Bywords. That is why the research has looked at the Bywords in a pragmatical way, for that reason the research has backed itself up by dates to find the rate of acts in Bywords.